Comparison of the Concentration of Local Microorganisms (MOL) in Stale Rice During the Composting Process - Ali, Haidina; Gustiana , Mely; Suyanto, Jipri; Susanty, Sri (Public Health of Indonesia, 2024)
Background: The symbiotic relationship between microorganisms, specifically decomposing bacteria, and organic material, such as organic waste, leads to the decomposition of the substance and its transformation into compost. Objective: The aim of this study is to assess the efficacy of local microorganisms (MOL) tape in accelerating the decomposition process of organic waste compost. Methods: This research used an experimental study strategy known as "control with posttest". This investigation was conducted utilising two distinct groups: the control group and the treatment group. Regarding the intervention group utilising indigenous microorganisms (MOL) stale rice, the research utilised two data analyses: univariate analysis, which involved presenting data in the form of frequency distribution tables, and bivariate analysis, which included conducting a one-way Anova test followed by an LSD test. Results: The findings indicated that the optimal dosage of a local microorganism (MOL) activator for compost formation was 25 ml, resulting in a duration of 11.6 days. The statistical analysis revealed a significant difference (p < 0.05) in the duration of compost formation between the dosage levels of 10 ml, 15 ml, 20 ml, and 25 ml of the local microorganism (MOL) activator. Conclusions: This research aims to explore the potential of MOL activators in accelerating the composting process of organic waste. By utilising MOL activators, it is anticipated that the problem of slow composting can be effectively addressed, offering a viable solution for the community. Moreover, the ease and affordability of producing MOL activators further enhance their practicality.